Phase Transitions in Development of Writing Fluency From a Complex Dynamic Systems Perspective. Issue 1 (24th December 2013) - Baba, Kyoko; Nitta, Ryo
<x xml:space="preserve">Abstract</x> This study explored patterns in L2 writing development by focusing on one of the linguistic features of texts (fluency) from a complex dynamic systems perspective. It investigated whether two English‐as‐a‐foreign‐language university students would experience discontinuous change (phase transition) in their writing fluency through repetition of a timed writing task. The students performed the task along with reflective writing once a week throughout the school year (30 times). Phase transitions were assessed against four criteria: sudden jumps, anomalous variance, divergence, and qualitative change in the attractor. The results suggest that both students underwent at least one phase transition. The findings imply the existence of "supra" patterns that could be revealed by longitudinal, multiple‐type observation.